On the undesirable repercussions of gender norms in an endogenous growth model - Ryo Sakamoto; Katsunori Minami (Osaka University, Institute of Social and Economic Research (ISER), 2024)
Sustainable growth has emerged as a critical policy challenge worldwide. We investigate the influence of conventional gender norms on fertility and economic growth to explain the phenomena recently observed across high-income countries. To this end, we construct an overlapping generations model with endogenous fertility and labor supply, incorporating gender norms and R&D activities. We demonstrate that conventional gender norms can impede fertility and economic growth. Specifically, when gender norms are sufficiently conservative, income growth stagnates and population erosion eventually occurs. Conversely, when gender norms are sufficiently less conservative, the economy follows a sustained growth path characterized by simultaneous growth in both population and income per capita. Our results underscore the need to address and correct gender norms to achieve sustainable growth and improve welfare.
Keywords: J13; J16; O40; 330; Gender norms; economic growth; fertility; domestic production